Rebranding Produk Keripik Tortilla Seaweed-Binar PPU Poklhasar Swakarya Bersama Kabupaten Penajam Paser Utara - Diniar Mungil Kurniawati; Menasita Mayantasari; Faisal Manta; Donny Pasunyar; Riola Montissa; Ahmad Yassar Sitompul; Muhammad Idris Al-Hakim; Achmad Farizul Hasmi; Fauzan Adzimi; Riki Herliansyah (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Poklahsar Swakarya Bersama is an MSME Group that focuses on processing and marketing activities, located in Tanjung Tengah Village, North Penajam Paser Regency (PPU) East Kalimantan Province with processed products made from seaweed. Currently, PPU Regency has been approved as the National Capital of Indonesia (IKN). One of the concentrations needed in moving the new capital is the readiness of the IKN buffer area. However, the essence of this community service activity is to improve the quality of MSMEs operating in the food sector, namely Poklahsar Swakarya Bersama. These improvement efforts must be developed through strengthening technology, branding and marketing to expand markets and business management. With the market strengthening program with branding and digital marketing, it is hoped that it will be able to expand and strengthen the target market. This rebranding activity is packaged with digital marketing training activities and selecting logo and packaging designs. The target market desired by Poklahsar Swakarya Bersama is seaweed tortilla chips which can be consumed by all ages and genders. Therefore, the selection of a new logo and packaging went through an audience stage with partners where several alternative designs had been created by the activity implementation team.